How product aesthetics cues efficacy beliefs of product performance. Issue 9 (4th April 2020) - Sundar, Aparna; Cao, Edita S.; Machleit, Karen A.
Abstract: Aesthetics of package design is an important consideration when consumers make purchase decisions. We argue that this is particularly the case for purchase decision of products in the beauty category. This paper advances current understanding of the role of packaging in product purchase behavior by identifying heuristic cues exhibited in packaging (i.e., that beautiful packaging is more effective at making the consumer more beautiful). Across a pilot field study and four lab studies, we demonstrate that package aesthetics informs inferences of how well the product can perform, which, in turn, drives purchase decisions. Importantly, we show that in the presence of a diagnostic cue such as a brand name, or an explicit promise (e.g. tagline of an advertisement), this effect is attenuated and rendered irrelevant. Further, we show that this effect is rendered ineffective to a category to which beauty is irrelevant. Hence, by signaling product efficacy, the beauty‐in‐a‐bottle heuristic appears to inform purchase decisions.